Oribatid mites (Acari: Oribatida) in sub-Arctic peatlands : a multidisciplinary investigation into climate change, permafrost dynamics and indicator values of subfossils - Markkula, Inkeri (fi=Turun yliopisto|en=University of Turku|, 2020)
Sub-Arctic peatland ecosystems are undergoing rapid changes due to climate warming. Palsa and peat plateau mires, northern peatlands with permafrost as a definitive character, are degrading particularly rapidly. Rising temperatures are causing permafrost thaw, leading to alterations in hydrology, vegetation structure and microhabitat diversity. At the same time, the microinvertebrate fauna, such as oribatid mites (Acari: Oribatida), of these mires remain poorly known. Oribatid mites are microscopic (0.1−1mm), mainly soil-dwelling arachnids, found in all terrestial ecosystems, where they function as decomposers of organic matter. With 11 000 species described worldwide, and densities reaching 200 000 individuals per square meter, oribatids are one of the most species-rich and abundant soil-living animal taxa. Despite this, oribatids are considered a poorly known animal group. Oribatid mites have been shown to be good bioindicators of natural and anthropogenic environmental change, but they are rarely included in studies detecting ecosystem dynamics in the sub-Arctic region. The aims of this thesis were to study the impacts of climate change on oribatid mite communities living in sub-Arctic peatlands, and to investigate if oribatid mites can be used as bioindicators in studies detecting historical permafrost dynamics. Data was collected from peatlands in Northern Fennoscandia, Siberia and Canada, and the studies included investigations of contemporary and past oribatid mite communities, covering a timescale 6000 years, as well as warming experiments. The results of this thesis show that permafrost thaw in peatlands leads to alterations in the species composition and dominance structure of oribatid communities. The direct impacts of warming on peatland-dwelling oribatid mites are season-dependent: findings revealed that summer warming had a positive and winter warming a negative impact on oribatid densities. Small-bodied oribatid mites belonging to the genus Suctobelba significantly increased in abundance under summertime warming. The taxon richness of oribatid mites was negatively affected by year-round warming. The results also reveal that oribatid mites are valuable indicators of past permafrost conditions in sub-Arctic peatlands. Three permafrost-indicator species, Carabodes labyrinthicus, Neoribates aurantiacus and Chamobates borealis, were recorded. This thesis provides novel information about the impacts of climate change on sub- Arctic oribatid mite communities. The studies highlight the conservational importance of palsa mires, and the importance of seasonal effects to be included in climate change studies. Moreover, findings of this thesis can help to understand the history of permafrost aggradation and degradation in peatlands, as oribatid mites can contribute to multi-proxy approaches aiming to reconstruct past environmental conditions. The results are significant, because understanding of past permafrost dynamics will help to predict future climate feedbacks and associated ecosystem shifts in changing sub-Arctic peatlands.

Ilmaston lämpeneminen aiheuttaa nopeita muutoksia subarktisissa suoekosysteemeissä Erityisen herkkiä lämpenemisen vaikutuksille ovat pohjoiset palsasuot, joille on tunnusomaista turpeesta muodostuneiden palsojen sisältämä ikirouta. Ilmaston lämpeneminen sulattaa palsasoiden ikiroutaa, mikä aiheuttaa muutoksia kosteusoloissa, kasvillisuuden rakenteissa ja mikroelinympäristöjen monimuotoisuudessa. Toisaalta palsasoiden mikroselkärangattomien, kuten sammalpunkkien (Acari: Oribatida), lajisto tunnetaan puutteellisesti. Sammalpunkit ovat mikroskooppisia (0.1−1 mm), pääasiassa maaperässä eläviä selkärangattomia, jotka toimivat hajottajina erilaisissa ekosysteemeissä. Sammalpunkkilajeja tunnetaan maailmasta noin 11 000, ja yhdellä neliömetrillä niitä voi elää 200 000 yksilöä. Runsaudestaan ja monimuotoisuudestaan huolimatta sammalpunkit luokitellaan puutteellisesti tunnetuksi eläinryhmäksi. Sammalpunkit ovat aiemmissa tutkimuksissa osoittautuneet hyviksi indikaattorilajeiksi, jotka voivat ilmentää ekosysteemeissä tapahtuvia muutoksia. Toistaiseksi sammalpunkkeja on kuitenkin käytetty subarktisten ekosysteemien muutosten tutkimisessa varsin vähän. Tämän työn tavoitteina oli tutkia, miten ilmaston lämpeneminen vaikuttaa subarktisilla soilla elävien sammalpunkkien yhteisöihin, sekä selvittää, voiko sammalpunkkeja käyttää bioindikaattorilajeina historiallisen ikiroutadynamiikan tutkimisessa. Tutkimuksen aineisto kerättiin Pohjois-Fennoskandian, Siperian ja Kanadan ikiroutasoilta. Tutkimuksissa kartoitettiin soiden tämänhetkistä sekä historiallista sammalpunkkilajistoa 6000 vuoden aikajänteellä. Ilmastonmuutoksen vaikutuksia sammalpunkkien yhteisöihin tutkittiin lisäksi lämmityskokeita käyttäen. Tutkimukset osoittivat, että ikiroudalla on tärkeä merkitys sammalpunkkien lajikoostumuksen muokkaajana, ja ikiroudan sulaminen johtaa muutoksin sammalpunkkien eliöyhteisöissä. Ilmaston lämpenemisen vaikutukset soilla eläviin sammalpunkkeihin riippuvat vuodenajasta: sammalpunkkien tiheydet kasvoivat, kun kesäaikainen lämpötila oli korkeampi, mutta vähenivät silloin kun vain talven lämpötilat nousivat. Erityisesti pienikokoiset, Suctobelba -sukuun kuuluvat punkit hyötyivät kesäaikaisesta lämpenemisestä. Ympärivuotinen lämpeneminen vaikutti negatiivisesti sammalpunkkien lajiston monimuotoisuuteen. Sammalpunkit osoittautuivat hyviksi ikiroudan indikaattoreiksi. Tutkimuksessa löydettiin kolme lajia, Carabodes labyrinthicus, Neoribates aurantiacus sekä Chamobates borealis, jotka ilmentävät vahvasti ikiroudan esiintymistä. Tämä väitöskirja tuo uutta tietoa ilmaston lämpenemisen vaikutuksista sammalpunkkien eliöyhteisöihin. Tutkimustulokset painottavat palsasoiden luonnonsuojelullista merkitystä sekä sitä, että ilmaston lämpenemisen vaikutuksia maaperän eliöyhteisöissä tutkittaessa tulisi vuodenaikojen vaikutus ottaa paremmin huomioon. Lisäksi, tämän tutkimuksen tulokset voivat auttaa ymmärtämään paremmin historiallista ikiroutadynamiikkaa subarktisilla soilla, sillä sammalpunkit tuovat niiden tutkimiseen yhden indikaattorin lisää. Menneiden ilmastonmuutosten ja niihin liittyvän ikiroutadynamiikan tutkiminen on ensisijaisen tärkeää, sillä se auttaa ennustamaan tulevia muutoksia subarktisissa ekosysteemeissä.